2021
DOI: 10.1088/1361-648x/ac02e4
|View full text |Cite
|
Sign up to set email alerts
|

Surface acoustic wave assisted depinning of magnetic domain walls

Abstract: We investigate the effects of high frequency strain on the depinning of magnetic domain walls in perpendicular anisotropy materials. Micron wide stripes of [Co(0.3nm)/Pt(0.6nm)]5 are patterned between a pair of identical inter-digital transducers that generate high frequency (114.8 MHz) standing surface acoustic waves. We use magneto-optical Kerr effect microscopy to characterize the thermally-assisted depinning of domain walls at defect sites within the strips. Our results show that the excitation of the doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Other proposals for manipulating DWs using strain include applying dynamic strain profiles and Dean et al [112] proposed using standing surface acoustic waves (SAWs) along the length of an IM magnetic nanowire to create an array of DW pinning sites. Subsequently, Adhikari et al [113] found that exciting DWs in an array of OOPM Co/Pt multilayer nanowires using SAWs (created using integrated digital transducers and shown in figure 6(a)) resulted in an increase in the DW depinning probabilities by approximately a factor of 10 (figure 6(b)). Technological proposals based upon strain-induced control of DWs include memories [114] and manipulation of magnetic beads in a fluid [115].…”
Section: Dw Motionmentioning
confidence: 99%
“…Other proposals for manipulating DWs using strain include applying dynamic strain profiles and Dean et al [112] proposed using standing surface acoustic waves (SAWs) along the length of an IM magnetic nanowire to create an array of DW pinning sites. Subsequently, Adhikari et al [113] found that exciting DWs in an array of OOPM Co/Pt multilayer nanowires using SAWs (created using integrated digital transducers and shown in figure 6(a)) resulted in an increase in the DW depinning probabilities by approximately a factor of 10 (figure 6(b)). Technological proposals based upon strain-induced control of DWs include memories [114] and manipulation of magnetic beads in a fluid [115].…”
Section: Dw Motionmentioning
confidence: 99%
“…11 Surface acoustic waves (SAWs) are acoustic waves traveling along the surface of a material exhibiting elasticity, which can introduce time-varying (dynamic) strain waves in the magnetic thin films. [16][17][18][19][20][21] Dean et al simulated the rea) Authors to whom correspondence should be addressed:…”
mentioning
confidence: 99%
“…22 Adhikari et al reported that a SAW can depin magnetic domain walls, increasing the probability of depinning between 4-9 times, and increasing the domain wall velocity in Co/Pt multilayers up to 8 times. 19,20 Thevenard et al experimentally demonstrated up to 60% coercivity reduction in an out-of-plane magnetized (Ga,Mn)(As,P) films at ∼40 K, showing the potential of SAWassisted magnetisation switching. 17 SAW-induced coercivity reduction and domain wall motion show significant potential for energy-efficient information storage and data processing devices, since the magnetisation switching is driven by voltage instead of current.…”
mentioning
confidence: 99%